PRE-MARRIED EDUCATION URGENTION AS AN EFFORT TO PREPARE WIFE HUSBANDS FOR MARRIAGE - Abdul Hadi Ismail (NOMOI Law Review, 2020)
The birth of BP4 was motivated by the high divorce rate, rampant child marriage and unhealthy polygamy.Over time, one of BP4's duties is to organize pre-marriage courses, as an effort to create asakinahhousehold, mawaddah wa rahmah.BP4 in its duties conducts pre-marital courses, provides material related to understanding marriage and domestic life, maintains good communication between prospective married couples, provides procedures for resolving conflicts in the household.Based on these conditions, BP4 has a heavy duty, function and role.This means that the good and bad of a marriage also depends on the functioning and role of the BP4.Keyword: Education, Pre-marriage, Husband and Wife, Marriage